Plasma vitamin C levels are associated with brain structural networks on MRI: A large cohort study - Haruka Nagaya; Keita Watanabe; Tomohiro Shintaku; Miho Sasaki; Jusei Kudo; Sera Kasai; Yuka Ishimoto; Kana Saito; Shuichi Matsuhashi; Taiki Koshiishi; Mizuki Imura; Amo Ozawa; et al. (PLoS ONE, 2026)
Background Neurodegenerative diseases significantly impact brain health in older adults, and although dietary vitamin C intake has been associated with a reduced risk of cognitive impairment, it remains unclear whether plasma vitamin C levels independently affect brain structure and neural connectivity. This study aimed to investigate whether plasma vitamin C levels were independently associated with brain volume and default mode network (DMN) connectivity in older adults. Methods All participants underwent 3T magnetic resonance imaging (MRI). Total intracranial volume (ICV), gray matter volume (GMV), and white matter volume (WMV) were calculated using CAT 12 in SPM 12. DMN connectivity was assessed using independent component analysis, based on shared GMV variance across voxels, and quantified by the loading coefficients. Multiple regression analysis was used to investigate the associations among brain volume, DMN connectivity measurements, and plasma vitamin C levels. These analyses were adjusted for potential confounders (age, sex, Mini-Mental State Examination score, diabetes, hypertension, hyperlipidemia, and education levels), and lifestyle factors (smoking history, drinking history, and physical activity). GMV/ICV ratio and WMV/ICV ratio were calculated to adjust for individual differences in head size. Results This cross-sectional study included 2,044 participants (median age, 69 years; females, 61.1%). Low plasma vitamin C levels were significantly and independently associated with the GMV/ICV ratio (p < 0.001) and DMN connectivity (p < 0.001). Conclusions In conclusion, our findings demonstrate that plasma vitamin C levels are positively associated with the structural integrity of the gray matter and DMN connectivity, generating the hypothesis that vitamin C may play a role in brain health.